Dismorfna telesna motnja - Župan, Anja (Zdravniški vestnik, 2011)
Background: Body dysmorphic disorder is a somatoform disorder, which is characterized by the patientćs preoccupation with a minor or imagined apperance defect. It has a reported prevalence of 0.7 % to 2.3 % in the general population. Prevalence among patients seeking aesthetic surgery is 6 %to 15 %. Body dysmorphic disorder appears to affect men and women equally. Comorbidity with other psychiatric disorders is frequent. Cosmetic medical treatment is ineffective in treating body dysmorphic disorder. Treatment with selective serotonin reuptake inhibitors and cognitive behavioral therapy appear to be more effective. Conclusions: Body dysmorphic disorder is a commonpsychiatric disorder, which needs to be addressed by the medical profession and the general public. By searching Medline, we found 577 articlesmatching body dysmorphic disorder . The disorder is well known by general public of Western countries, especially USA, but is less known in Slovenia. As patients often pursue cosmetic procedures and aesthetic surgery, it is important that medical staff, especially providers of cosmetic surgical and minimally invasive treatments, are able to identify them and refer them for appropriate mental health care.
Keywords: estetska kirurgija; Etiology; Kirurgija plastična; psihiatrija; Psihoterapija; psychiatry and clinical psychology; Psychotherapy; Serotonin Uptake Inhibitors; Serotoninski privzem, inhibitorji; Somatoform Disorders; Somatoformne motnje; Surgery, Plastic; Therapy; zdravljenje